Optimization of Camat Role In Malay Community Empowerment (Study in Bina Widya District, Pekanbaru City) - Satya Haprabu Wibisono; Umi Muslikhah; Wira Atma Hajri; Lidia Febrianti; Halimah Nur Izzati; Monika Melina; Faishal Taufiqurrahman (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2021)
Abstract The district head has delegated authority, which is the delegation of authority from the regent/mayor. The delegation of authority includes aspects of service to the community which include: licensing, recommendations, coordination, guidance, supervision, facilitation, determination, implementation and other powers that are delegated including the social welfare of the people in their area. This research examines the optimization of the role of sub-district heads in empowering Malay communities, especially those in the Bina Widya sub-district, Pekanbaru City. This study uses a sociological juridical method approach with the aim of knowing how the sub-district head plays a role in community empowerment at research locations that have been determined and reviewed with existing laws and regulations. The results showed that the role of the sub-district head in community empowerment, especially in the field of social welfare, was still not optimal. This was evident from the uneven distribution of social assistance funds to people in need in the BinaWidya sub-district area.